2018
DOI: 10.1117/1.jbo.23.10.106003
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical quantitative in-vivo assessment of skin tissue vascularity in radiation-induced fibrosis with optical coherence tomography

Abstract: Radiation therapy (RT) is widely and effectively used for cancer treatment but can also cause deleterious side effects, such as a late-toxicity complication called radiation-induced fibrosis (RIF). Accurate diagnosis of RIF requires analysis of histological sections to assess extracellular matrix infiltration. This is invasive, prone to sampling limitations, and thus rarely used; instead, current practice relies on subjective clinical surrogates, including visual observation, palpation, and patient symptomatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…The irradiated skin was thicker than the control in both neutral and abducted positions. This is consistent with epidermal thickening described post radiation therapy [23] while the thinner subcutaneous adipose tissue nding is consistent with a previous study of post irradiation neck brosis [24] .…”
Section: Discussionsupporting
confidence: 92%
“…The irradiated skin was thicker than the control in both neutral and abducted positions. This is consistent with epidermal thickening described post radiation therapy [23] while the thinner subcutaneous adipose tissue nding is consistent with a previous study of post irradiation neck brosis [24] .…”
Section: Discussionsupporting
confidence: 92%
“…Demidov et al created radiation injuries in mice and imaged the area using SV-OCT. They were able to find significant differences between irradiated tissue and healthy tissue using vessel diameter measured from the SV-OCT images, which conform to the findings from histology-based methods 27 . These metrics have proven important in tracking angiogenesis and tumor progression, and can be applied to HHT lesions throughout a course of treatment; however, there is still a need to develop metrics tailored to progression monitoring of the unique morphology of telangiectases.…”
Section: Introductionsupporting
confidence: 74%
“…To do this properly in 3D, however, so as to furnish additional helpful visual information will require more research; this will also be pursued in future studies and be reported in a separate publication. For the remainder of this work we thus display the lymphatics/nerves and blood angiograms separately: blood microvasculature depth-encoded in RGB color space as described previously (green-yellow-red-grey shallow to deep color map) [45] and lymphatics/nerves in a grey-scale color map.…”
Section: Microvasculature (Blood and Lymph) And Nerves Detectionmentioning
confidence: 99%